How social marketing can change the world - Hastings, Gerard (Henry Stewart Talks, 2009)
Change is in the air, Global warming, Basic principles of marketing, Learning from commerce: why should the devil have all the best tunes?, Competitive analysis, Putting it into practice, Relationship marketing, Social marketing planning, Manifesto